2011
DOI: 10.1007/s00268-011-1331-0
|View full text |Cite
|
Sign up to set email alerts
|

How to Avoid Postoperative Liver Failure: A Novel Method

Abstract: This technique induced rapid growth of the FLR, greater than that reported with portal vein occlusion alone. It represents a promising advance in oncological liver surgery that readdresses the current management of patients with primarily unresectable liver disease. Such a revolutionary strategy allows a two-stage surgical approach during a single hospital stay and without PLF. However, further research is needed to determine the long-term outcomes of this technique and to explain the occurrence of such enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
73
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 13 publications
5
73
0
11
Order By: Relevance
“…In patient presented above, the ratio of FLR hypertrophy was 98% at 11 days, significantly higher than those reported with PVL. The higher hypertrophy ratio achieved by ALPPS procedure in the patient presented above is similar to those reported by other authors (22)(23)(24), who revealed a statistically significant increase in FLR volume after ALPPS than in patients undergoing PVE/PVL, allowing the performance of R0 resections in almost 100% of patients subjected to this new approach (25,26). Moreover, recent studies revealed that in patients who failed to achieve sufficient FLR hypertrophy after PVE, the performance of ALPPS was an effective strategy, able to induce a FLR gain which allowed subsequent R0 resection (26;27).…”
Section: Discussion Discussionsupporting
confidence: 80%
“…In patient presented above, the ratio of FLR hypertrophy was 98% at 11 days, significantly higher than those reported with PVL. The higher hypertrophy ratio achieved by ALPPS procedure in the patient presented above is similar to those reported by other authors (22)(23)(24), who revealed a statistically significant increase in FLR volume after ALPPS than in patients undergoing PVE/PVL, allowing the performance of R0 resections in almost 100% of patients subjected to this new approach (25,26). Moreover, recent studies revealed that in patients who failed to achieve sufficient FLR hypertrophy after PVE, the performance of ALPPS was an effective strategy, able to induce a FLR gain which allowed subsequent R0 resection (26;27).…”
Section: Discussion Discussionsupporting
confidence: 80%
“…Luego de una mediana de intervalo de 9 días, la mediana de volumen del lóbulo izquierdo fue de 536 cc, con un delta de volumen de 225 cc, y un incremento de volumen de 74% 3 . numerosos artículos y comentarios han sido posteriormente publicados al respecto 6,[16][17][18][19][20][21] .…”
Section: Discussionunclassified
“…En este caso el rol de la bipartición es evidente, ya que no se produjo hipertrofia del lóbulo izquierdo cuando sólo se ligó la vena porta derecha. Los resultados obtenidos a corto plazo en nuestra paciente son similares a los reportados en la literatura existente 6,[16][17][18][19][20][21] .…”
Section: Discussionunclassified
“…1,2,3 The development of ALPPS appears to have been at least in part by serendipity: initially described in a single patient with perihilar cholangiocarcinoma and then tested in a series of patients with extensive colorectal liver metastases. Early reports suggested there was a very high risk or peri-operative mortality but at the same time it appeared to offer hope for patients with a high burden of disease and as a result there were both strong proponents and opponents for this innovative procedure at an early stage and much argument remains today.…”
mentioning
confidence: 99%